The Role of IL-6, 8, and 10, sTNFr, CRP, and Pancreatic Elastase in the Prediction of Systemic Complications in Patients with Acute Pancreatitis. (12th February 2013) - Fisic, E.; Poropat, G.; Bilic-Zulle, L.; Licul, V.; Milic, S.; Stimac, D.
Abstract : Background and Aim . Early assessment of severity in acute pancreatitis (AP) is a key measure to provide rational and effective management. The aim of our study is to determine the prognostic value of interleukins (IL) 6, 8, and 10, soluble receptor for tumor necrosis factor (sTNFr), pancreatic elastase (E1), and C-reactive protein (CRP) as predictors of systemic complications in AP. Patients and Methods . A hundred and fifty patients with confirmed AP were enrolled in the study. The severity of AP was defined according to Atlanta criteria. Measurements of interleukins and sTNFr were performed on the first day of admission. CRP and E1 levels were assessed on admission and after 48 hours. ROC analysis was performed for all parameters. Results . Interleukins and sTNFr significantly differentiated patients with systemic complications from those without. Elevation of IL-6 showed the highest significance as a predictor (P = 0.001 ). CRP and elastase levels did not differ between mild and severe cases on admission, but reached statistical significance when measured on the third day (P = 0.002 and P = 0.001, resp.). Conclusion . Our study confirmed that IL-6, IL-8, IL-10, and sTNFr measured on admission, and CRP and pancreatic elastase measured on third day of admission represent valuable prognostic factors of severity and systemic complications of AP.